The Enantioselective Generation of Bridgehead Enolates - Kirk, Douglas Thomas (2003)
Chapter One gives an introduction to the key concepts of bridgehead alkene formation and its relevance to the formation of bridgehead enolates of ketones including a review of bridgehead enolates in synthesis. The review is limited to the generation of bridgehead carbanions alpha to a carbonyl group and does not cover bridgehead cations, radicals or any anions except those already mentioned. In addition, a brief introduction to chiral base methodology and a review of the latest developments is included. Chapter Two describes the generation of bridgehead enolates in various bridged bicyclic ketones using chiral and achiral lithium amide bases and their subsequent interception with chlorotrimethylsilane. The chiral bridgehead silanes resulting from enantioselective deprotonation were shown to undergo silyl exchange reactions with TBAT as fluoride source in the presence of various electrophiles. Chapter Three describes a review of bridgehead enolates of imides and describes the extension of the developed methodology in Chapter Two to the generation and trapping of bridgehead enolates in bridged bicyclic imides and lactams. In addition bridgehead enolates are shown to react in the presence of non-classical in situ electrophiles such as methyl iodide, allyl bromide, benzyl bromide, prenyl bromide and pivaloyl chloride in high yield and enantioselectivity. The secondary bridgehead deprotonation of monosubstituted imides was also achieved resulting in double bridgehead functionalised products with high ee. The bridgehead silanes are shown to undergo silyl exchange reactions and display silyl directed regioselective reduction and thionation reactions. The mechanism of deprotonation, comparison to known examples and the origin of bridgehead carbanion stability are discussed. Chapter Four contains the experimental procedures and analytical data for the preparation of the novel compounds described herein followed by the appendix of selected NMR and X-ray data.